Molecular weight variations of kerogen during maturation with MALDI-TOF-MS. (1st June 2020) - Lee, Hyeonseok; Abarghani, Arash; Liu, Bo; Shokouhimehr, Mohammadreza; Ostadhassan, Mehdi
Abstract: Kerogen is an amorphous organic matter (AOM) in fine grain sediments, which produces petroleum and other byproducts when subjected to adequate pressure and temperature (deep burial conditions). Chemical characteristics of kerogen by considering its biogenic origin, depositional environment, and thermal maturity has been studied extensively with different analytical methods, though its molecular structure is still not fully known. In this study, conventional geochemical methods were used to screen bulk rock aliquots from the Bakken Shale with varying thermal maturities. Organic matter was isolated from the mineral matrix and then a mass spectrometry method was utilized to quantify molecular weight distribution (MWD) of four different kerogens at various thermal maturity levels (immature to late mature). Furthermore, to complement mass spectrometry, Fourier transform infrared (FTIR) spectroscopy was employed as a qualitative chemical and structural investigation technique. The MWD of four samples was obtained by matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry, and the results are correlated with the absorption indices (CH3 /CH2 ratio and aromaticity) calculated from the FTIR attenuated total reflectance (ATR) method. The results showed when the degree of maturity increases, the aliphatic length shortens, and the branching develops, as well as the aromatic structure becomes more abundant. Moreover, based on the MWD results, higher maturity kerogen samples would consist of larger size molecular structures, which are recognized as more developed aromatic, and aliphatic branching stretches. The combination of infrared spectroscopy (AFT-FTIR) and mass spectrometry (MALDI-TOF) provided MWD variations in organic matter samples as a function of maturity based on varying absorption indices and revealed the rate of change in molecular mass populations as a function of thermal maturity in a type II kerogen.